Psychophysiological responses to Salsa dance. - Laura Guidetti; Cosme Franklim Buzzachera; Gian Pietro Emerenziani; Marco Meucci; Francisco Saavedra; Maria Chiara Gallotta; Carlo Baldari (PLoS ONE, 2015)
Speculation exists whether dance provides physiological stimuli adequate to promote health and fitness benefits. Unfortunately, research to date has not addressed the affective and exertional responses to dance. These responses are of interest as positive affective and exertional responses experienced during physical activity may play an important role in predicting adherence. The present study aims to examine the psychophysiological responses of different Salsa dance styles. Ten pairs of dancers performed two different structured lessons of Salsa dance, including Typical Salsa and Rueda de Casino lessons, and a non-structured Salsa dance at a night club. Physiological responses (i.e., percent of heart rate reserve; %HRR) were continuously assessed and perceived exertion and affective valence were rated every 15 min throughout the trials. %HRR responses differed between the Salsa dance styles (%HRR from 41.3 to 51.9%), and participants were dancing at intensities near their ventilatory threshold. Specifically, Typical Salsa lesson elicited lower %HRR responses than Rueda de Casino lesson (p < 0.05), but similar %HRR responses to Salsa dance at a night club condition (p > 0.05). Surprisingly, exertional (from 8 to 11) and affective (from +3 to +5) responses were unaffected by Salsa dance styles (p > 0.05). These data support that different Salsa dance styles provide physiological stimuli adequate to promote health and fitness benefits, and perhaps more importantly, produce pleasurable experiences, which in turn might lead to an increase in adherence to Salsa dancing which likely provides exercise-like health benefits.